2013
DOI: 10.1016/j.neuropharm.2012.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of methamphetamine seeking by the mGluR2/3 agonist LY379268 in rats with histories of restricted and escalated self-administration

Abstract: Recent findings implicate group II metabotropic glutamate receptors (mGluR2/3) in the reinforcing effects of psychostimulants and have identified these receptors as potential treatment targets for drug addiction. Here, we investigated the effects of mGluR2/3 stimulation on cue- and drug-primed reinstatement in rats with different histories of methamphetamine (METH) self-administration training, under two conditions: 16 daily sessions of short access (90 min/day, ShA), or 8 daily sessions of short access follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 63 publications
(104 reference statements)
2
36
0
Order By: Relevance
“…In fact, beside cocaine, LY379268 was efficacious in blocking cue-and contextinduced reinstatement of alcohol, heroin, methamphetamine, nicotine, and natural reward-seeking (Bossert et al, 2004(Bossert et al, , 2005(Bossert et al, , 2006aKufahl et al, 2011Kufahl et al, , 2013Liechti et al, 2007;Zhao et al, 2006). This wide spectrum ranging from addictive to non-addictive rewards may suggest a more general role for mGluR2/3 in the conditioned effect of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, beside cocaine, LY379268 was efficacious in blocking cue-and contextinduced reinstatement of alcohol, heroin, methamphetamine, nicotine, and natural reward-seeking (Bossert et al, 2004(Bossert et al, , 2005(Bossert et al, , 2006aKufahl et al, 2011Kufahl et al, , 2013Liechti et al, 2007;Zhao et al, 2006). This wide spectrum ranging from addictive to non-addictive rewards may suggest a more general role for mGluR2/3 in the conditioned effect of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that group II (mGluR2 and mGluR3) agonists can affect addiction-related behaviors in animal models. For example, the orthosteric mGluR2/3 agonist LY379268 has been shown to attenuate contextual as well as cue-induced heroin seeking (Bossert et al, 2005;Bossert et al, 2004), cue-induced methamphetamine seeking (Kufahl et al, 2013), incubation of cocaine-craving (Lu et al, 2007), and cue-induced nicotine seeking (Liechti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In rats, systemic injections of LY379268 or related mGluR2/3 agonists decrease discriminative-cue-induced reinstatement of cocaine seeking and context-induced reinstatement of heroin seeking (12, 13), decrease discrete cue-induced reinstatement of heroin seeking (14), cocaine priming-induced reinstatement (15), spontaneous recovery of alcohol seeking (16), cue-induced cocaine seeking (17), and discrete cue- and drug priming-induced reinstatement of methamphetamine seeking (18). LY379268 injections also decrease cocaine priming-induced reinstatement in squirrel monkeys (19).…”
Section: Introductionmentioning
confidence: 99%